Bewusstseinsstörungen und Koma - Erbguth, Frank (DMW - Deutsche Medizinische Wochenschrift, 2019)
Cerebral diseases such as epileptic seizures, cerebral hemorrhages or meningoencephalitis are the primary cause of approximately 50 % of non-traumatic acute disorders of consciousness. For the differential diagnosis, history and other symptoms are important such as hemiplegia, signs of brain stem dysfunction, meningism or headache. Metabolic, endocrinologic, toxicologic or electrolytic causes of coma usually can be diagnosed by laboratory examinations. Anamnestic informations, body inspection, clinical neurological examination as well as laboratory and imaging findings have to be added and categorized by a multilevel composition to establish a conclusive diagnosis. Simultaneously therapeutic measures for suspected primary cerebral diseases must be initiated, for example a rapid antibiotic treatment in case of a possible bacterial meningitis. A fast and structured diagnostic approach is crucial for ensuring a good prognosis and helps to miss relevant diagnostic steps. Potential diagnostic and therapeutic pitfalls must be kept in mind.
Keywords: akute Bewusstseinsstörung; Koma; Differenzialdiagnostik; Management; Fallstricke